The hydrometra case in a maltese goat - İbrahim Taşal; M. Bozkurt Ataman; D. Ali Dinç (Eurasian Journal of Veterinary Sciences)
A real-time ultrasonographic diagnosis of a hydrometra case In a six-years-old Maltese Goat was described This was confirmed at postmortem examination.